Experiential marketing : case studies in customer experience - Batat, Wided (New York : Routledge, 2021)
"Experiential marketing has become an indispensable tool for all types of businesses across multiple sectors. This book provides an all-encompassing, practical, and conceptual map of contemporary experiential case studies, which together offer insights into this exciting approach to customer experience. Experiential Marketing incorporates 36 international case studies from 12 key sectors, from technology, consumer goods, and B2B to luxury, events, and tourism sectors. With a selection of case studies from leading brands, such as Coca Cola, Nutella, Chanel, NASA, the New York Times, Pfizer, and Amtrak, the reader will learn and practice the experiential marketing tools and strategies through these examples. Expert testimonials, practical applied exercises, and the author's online videos provide both theoretical foundations and concrete application. This is a must-read for advanced undergraduate and postgraduate Marketing and Customer Experience students and an excellent teaching resource. It should also be of great use to and practitioners - particularly those studying for professional qualifications - who are interested in learning experiential marketing strategies and developing knowledge about the way big brands in different sectors are designing the customer experience online and offline. Online material includes lecture slides, a test bank of questions, instructor's manual and explanatory videos"--
Keywords: The customer experience in the sports events and entertainment sector; The customer experience in the banking and insurance sector; Target marketing; Relationship marketing